The Earth in God's economy : reflections on the narrative of God's work - Conradie, Ernst M. (Scriptura, 2008)
This essay is an abbreviated version of an inaugural lecture, read on 24 October 2007 at the University of the Western Cape. It investigates the role of cosmological narratives that help people to understand where they come from, who they are, how they can cope with the demands of life and with evil, and where they are going to. It focuses on one such a narrative, namely the Christian story of God's work of creation, evolution, the emergence of human beings and human culture, the distortions resulting from human sin, God's providence, redemption, the formation of the church, its ministries and missions and the consummation of all things. These themes have traditionally been captured under the notion of 'God's economy'. This term is derived from the Greek word oikos which is understood in the Christian tradition as 'the whole household of God'. In contemporary ecumenical theology this term provides a clue as to how the moral of this story may be understood to address ecological degradation, economic injustices and ecumenical fellowship. The argument of the essay is that a retrieval of the underlying narrative structure of the story of God's work can help to avoid the ways in which one 'chapter' of the story tends to be subsumed under another.